Lost plantation : the rise and fall of Seven Oaks - Matrana, Marc R. (Jefferson historical series ;, 2006)
Along the fertile banks of the Mississippi River across from New Orleans, planter Camille Zeringue transformed a mediocre colonial plantation into a thriving gem of antebellum sugar production, complete with a columned mansion known as Seven Oaks. Under the moss-strewn oaks, the privileged master nurtured his own family, but enslaved many others. Excelling at agriculture, business, an ambitious canal enterprise, and local politics, Zeringue ascended to the very pinnacle of southern society. But his empire soon came crashing down. After the ravages of the Civil War and a nasty battle with a rai.